Time Token Strategy to Enhance Students’ Speaking Ability - Nasution, Fitri Ramadani; Zainuddin, Zainuddin; Minda, Sri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research purpose to describe the effect of time token strategy to students speaking ability. This research was applied quantitative research with experimental method. The sample was the students at grade XI of MA Nurul Falah Tamosu, consists of 60 students. The instrument of this research is tests. After using time token strategy, the mean score of experimental class it is higher after using time token strategy. The mean score of post-test in experimental class was 70.4 and it was classified into poor category, while the mean score of post-test in control class was 58 and it was classified into poor category. The researcher used independent sample t-test to examine the hypothesis. The result found that tcount was 4.188 and ttable was 2.000 (4.188 2.000). It means that Ha is accepted and H0 is rejected. So, there is a significant effect of time token strategy on students speaking ability at grade XI of MA Nurul Falah Tamosu.